Optimalization Image Of Turbo Spin Echo (TSE) With Pre Saturation And Gradient Moment Nulling (GMN) To Reduce Flow Artifact On MRI Cervical - Kiki Rohmatul Ula (Universitas Airlangga, 2019)
ABSTRACTThe research of Optimization Image of Turbo Spin Echo (TSE) with Pre saturation and Gradient Moment Nulling (GMN) to reduce flow artifact on MRI Cervical has been done. The purpose of this research is to know the effect of pre saturation and gradient moment nulling (GMN) on cervical MRI and determine optimal image to reduce flow artifact. This research used four treatment variations that were without pre saturation and without flow compensation (GMN), with pre saturation, with flow compensation (GMN), and with both pre saturation and flow compensation (GMN) on sequence T2-weighting TSE sagital on cervical MRI. The quantitative analysis done by using Region of Interest (ROI) on MRI image then analyzed signal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR). The best effect and image quality obtained by pre saturation and flow compensation (GMN) treatment with SNR value on tissue was 328,7 at vertebra cervical, 278,6 at spinal cord, 366,6 at discus, 596,3 at CSF. While CNR tissue value was 78,6 at vertebra cervical, 257,6 at spinal cord, 274,8 at discus, and336,3 at CSF followed by the decrease of flow artifact in the amount of 160,4. Conclusion shows that the image with both pre saturation and flow compensation (GMN) treatment on T2 TSE sagital can reduce flow artifact signal on the spinal cord tissue. Keywords : Pre saturation, flow compensation, gradient moment nulling (GMN), MRI Cervical.